2010
DOI: 10.1002/etc.390
|View full text |Cite
|
Sign up to set email alerts
|

Development of an enzyme‐linked immunosorbent assay for quantifying vitellogenin in Pacific salmon and assessment of field exposure to environmental estrogens

Abstract: A competitive enzyme-linked immunosorbent assay was developed to quantitate vitellogenin (VTG) in plasma and serum of coho (Oncorhynchus kisutch) and chinook (O. tshawytscha) salmon. The working range of the assay was 9 to 313 ng/ml (80-20% binding), with 50% binding at 54 ng/ml. The intra-assay and interassay variations at approximately 50% binding were 8.1% (n = 9) and 9.0% (n = 9), respectively. Dilution curves of plasma or serum from coho and chinook females and estrogen-treated males were parallel to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Moreover, the parallelism observed between the Lv standard curve and WBH dilution curves of E 2 -exposed male guppy demonstrated that anti-Lv antibody recognized Lv and Vtg similarly. In addition, the ELISA did not detect positive signal in control male WBH, indicating that this assay was very specific to Vtg 30 , 31 . The above results confirmed that the sandwich ELISA established in the present study could accurately quantify guppy Vtg.…”
Section: Discussionmentioning
confidence: 90%
“…Moreover, the parallelism observed between the Lv standard curve and WBH dilution curves of E 2 -exposed male guppy demonstrated that anti-Lv antibody recognized Lv and Vtg similarly. In addition, the ELISA did not detect positive signal in control male WBH, indicating that this assay was very specific to Vtg 30 , 31 . The above results confirmed that the sandwich ELISA established in the present study could accurately quantify guppy Vtg.…”
Section: Discussionmentioning
confidence: 90%
“…A quantitative and sensitive EIA was developed from the methods outlined in Peck et al (2011) using a polyclonal, rabbit anti-Atlantic salmon Vtg antibody, AA-1 (Biosense Laboratories AS, Bergen, Norway). Costar, 96-well microtiter plates (#3369, Corning Life Sciences, Tewksbury, MA) were coated with 60 ng/ml Atlantic salmon vitellogenin (#9902, Biosense Laboratories, Bergen, Norway) in 0.05 M Na 2 CO 3 and incubated overnight at 4 • C. The following day, plates were washed with cold phosphate-buffered saline (PBS) with 0.05% Tween-20 (Sigma-Aldrich), pH 7.2 (PBST) and blocked with PBST with 2% milk powder overnight at 4 • C. Samples or standards were mixed with the primary antibody (in PBST with 1% milk powder).…”
Section: Vtg Enzyme Immunoassay (Eia)mentioning
confidence: 99%
“…Costar, 96-well microtiter plates (#3369, Corning Life Sciences, Tewksbury, MA) were coated with 60 ng/ml Atlantic salmon vitellogenin (#9902, Biosense Laboratories, Bergen, Norway) in 0.05 M Na 2 CO 3 and incubated overnight at 4 • C. The following day, plates were washed with cold phosphate-buffered saline (PBS) with 0.05% Tween-20 (Sigma-Aldrich), pH 7.2 (PBST) and blocked with PBST with 2% milk powder overnight at 4 • C. Samples or standards were mixed with the primary antibody (in PBST with 1% milk powder). Samples were diluted a minimum of 1:100 to minimize interference and false-positive readings where Vtg was low (Peck et al, 2011) up to 1:10,000 for samples with high Vtg content. These were mixed at 4 • C overnight on a rotary shaker.…”
Section: Vtg Enzyme Immunoassay (Eia)mentioning
confidence: 99%
“…As such, they may elicit toxicological modes of action other than what is expected from their intended use in humans and livestock . Recent studies indicating endocrine disruption in juvenile salmon from Puget Sound and evidence of vitellogenin production, histopathological lesions, and other estrogen‐induced disorders in male English sole from urban bays in Puget Sound may indicate aquatic species are exposed to endocrine disrupting substances such as PPCPs.…”
Section: Introductionmentioning
confidence: 99%